Upaya Pembiasaan Literasi Terhadap Minat Baca Siswa SMPN 2 Jasinga Desa Cikopomayak - Mohamad Najib; Siti Nurhasanah; Eva Fuziah (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2025)
The low reading interest of students today greatly affects the quality of the Indonesian nation, because with low interest in reading, they cannot know and follow the development of science and information in the world, which in the end will have an impact on the backwardness of the Indonesian nation. Therefore, the application of literacy culture in schools should be implemented so that students have the habit and interest in reading. This study aims to motivate students to be more diligent and interested in the world of literacy and reading. This research uses quantitative methods, where we go directly to the field to find data. The result of this research is that there is a relationship or closeness between literacy and students' reading interest.